Politics and the passions, 1500-1850 - Kahn, Victoria Ann; Saccamano, Neil, 1952-; Coli, Daniela (Princeton University Press, 2006)
Focusing on the new theories of human motivation that emerged during the transition from feudalism to the modern period, this is the first book of new essays on the relationship between politics and the passions from Machiavelli to Bentham. Contributors address the crisis of moral and philosophical discourse in the early modern period; the necessity of inventing a new way of describing the relation between reflection and action, and private and public selves; the disciplinary regulation of the body; and the ideological constitution of identity. The collection as a whole asks whether a discours.